ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PADA PERBANKAN YANG GO PUBLIK DI BURSA EFEK INDONESIA (BEI) - EFENDI, HENDRIYAN JOYO; FERMAYANI, RICHE (STIE Perbankan Indonesia, 2018)
The formulation problem of this research is about the extent of financial performance (ROA) on Capital Aduquacy Ratio (CAR), Non Performing Loan (NPL), Operational Cost and Operational Income (BOPO), Net Interest Margin (NIM) and Loan to Deposite Ratio (LDR). Secondary data was collecting from download the commercial financial report from year 2009-2013 of the banks which registered in Indonesia Stock Exchange on internet media by www.idx.co.id and ICMD (Indonesia Capital Market Directory). The result of this research shown that variable of NIM, and BOPO have a significant influence to financial performance (ROA) banks, but variable CAR, NPL, and LDR not significant influence to financial performance. Test F show that variable CAR, NPL, BOPO, NIM, and LDR have influence to financial performance (ROA) banks. On the result test of determination regression (R2) can be seen that explanation capability explanation of Independent variable CAN, NPL, BOPO, NIM, and LDR to dependent variable (ROA) was 59,2%, meanwhile the residu has explain by another factor which did not mantion on this research.